A citation network analysis of sustainability development in liner shipping management: a review of the literature and policy implications. Issue 1 (2nd January 2020) - Vejvar, Markus; Lai, Kee-Hung; Lo, Chris K. Y.
ABSTRACT: Based on an analysis of 253 related papers drawn from the Web of Science database, this study examines holistic sustainability research in liner shipping management literature using a citation network analysis (CNA) approach followed by a qualitative analysis of findings. We identify four major research domains, namely shipping performance, port selection and management, shipping markets, and environment, as well as related sub-domains of shipping performance. We discuss the current research trends and focal issues in these domains with a focus on their implications for policy development. Our results indicate that while the sustainability discourse in the literature has developed and matured significantly over the last decade, generating valuable insights for practitioners and regulators alike, it still struggles with blurry terminology and a lack of holistic frameworks jointly addressing the different aspects of sustainability: Economic considerations of liner shipping are still the main concern, while environmental and social issues are less regarded in the academic discourse. Furthermore, we identify a dearth of studies rooted in managerial or economic theory. In this regard, our study provides insights on the scope of the holistic sustainability discourse in liner shipping management, its contributions to theory and practice, and its implications for the further development of policies addressing sustainability in liner shipping management. We advocate further construct development for sustainability in liner shipping, as well as empirical tests of the antecedents of sustainability practice adoption in the industry for future research.